Chronic ethanol alters network activity and endocannabinoid signaling in the prefrontal cortex - Pava, Matthew J.; Woodward, John J. (Frontiers in Integrative Neuroscience, 2014)
Chronic use of alcohol is associated with structural and functional alterations in brain areas that subserve cognitive processes. Of particular importance is the prefrontal cortex (PFC) that is involved in higher order behaviors such as decision making, risk assessment and judgment. Understanding the mechanisms that underlie alcohol's effects on PFC function is important for developing strategies to overcome the cognitive deficits that may predispose individuals to relapse. Our previous studies showed that acutely applied ethanol inhibits network activity in slices of prefrontal cortex and that exogenous and endogenous cannabinoids modulate up-state dynamics. In the present study, we examined the effects of repeated alcohol exposure on cannabinoid regulation of up-states in slice cultures of the prefrontal cortex. Compared to controls, up-state duration, but not amplitude was enhanced when measured 4 days after a 10 day ethanol exposure (44 mM ethanol; equivalent to 0.2% blood ethanol). Administration of the CB1 agonist WIN 55,212-2 enhanced the amplitude of up-states in control cultures but not in those treated previously with ethanol. This lack of effect occurred in the absence of any noticeable change in CB1 receptor protein expression. Chronic ethanol treatment and withdrawal also blunted WIN's inhibition of electrically evoked GABA IPSCs in layer II/III pyramidal neurons but not those in layer V/VI. WIN inhibited the amplitude of spontaneous GABA IPSCs in both layers and the magnitude of this effect was not altered by ethanol treatment. However, in layer V/VI neurons, WIN's effect on sIPSC frequency was greater in ethanol treated cultures. WIN also inhibited electrically evoked NMDA EPSCs in both layer II/III and V/VI neurons but this action was unaffected by ethanol treatment and withdrawal. Overall, these results suggest that ethanol's down-regulation of cannabinoid signaling results in altered network activity in the prefrontal cortex.